2011
DOI: 10.1139/f2011-095
|View full text |Cite
|
Sign up to set email alerts
|

The relative role of environmental, spatial, and land-use patterns in explaining aquatic macrophyte community composition

Abstract: Quantifying the relative role of environmental and spatial factors to understand patterns in community composition is a fundamental goal of community ecology. We applied a tested and repeatable point-intercept sampling method to aquatic macrophyte assemblages in 225 Wisconsin lakes to understand the ability of environmental, land-use, and spatial patterns to explain aquatic plant distribution and abundance. Using a variation partitioning framework in conjunction with Moran eigenvector maps we found that enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 45 publications
8
55
1
1
Order By: Relevance
“…We revealed that the variables associated with altitude and in-stream habitats best accounted for the largest amount of variability in our macroinvertebrate data set, supporting the more important determinants of local environmental factors than broad or regional parameters [16,44]. The importance and role of local environmental variables have also been highlighted in other aquatic communities: aquatic macrophytes [45], freshwater phytoplankton [46], benthic diatoms [44], intertidal macroinvertebrates [47], and fish [48]. However, a comprehensive understanding of multispatial scales is needed because of significant correlations between macrohabitat and microhabitat characteristics, depending on the relative size of the area studied [3].…”
Section: Environmental Relationships With Macroinvertebrate Distributionsupporting
confidence: 65%
“…We revealed that the variables associated with altitude and in-stream habitats best accounted for the largest amount of variability in our macroinvertebrate data set, supporting the more important determinants of local environmental factors than broad or regional parameters [16,44]. The importance and role of local environmental variables have also been highlighted in other aquatic communities: aquatic macrophytes [45], freshwater phytoplankton [46], benthic diatoms [44], intertidal macroinvertebrates [47], and fish [48]. However, a comprehensive understanding of multispatial scales is needed because of significant correlations between macrohabitat and microhabitat characteristics, depending on the relative size of the area studied [3].…”
Section: Environmental Relationships With Macroinvertebrate Distributionsupporting
confidence: 65%
“…One biological group showing context dependency has been aquatic macrophytes, many of which are distributed around the world due to efficient dispersal abilities and colonization strategies (Santamaría 2002; Chambers et al 2008). Environmental filtering has thus often overruled spatial factors in explaining variation in macrophyte community structure (Capers et al 2010; Mikulyuk et al 2011; Alahuhta et al 2013; Viana et al 2014), although opposite patterns have been found in some metacommunities (Hájek et al 2011; Padial et al 2014). These conflicting patterns for aquatic macrophyte metacommunities call for a more holistic comparative analysis including data sets with identical explanatory variables from different regions globally.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors are known to have an influence on the presence and abundance of aquatic macrophytes, for instance, herbivorism (Lodge, 1991;Pipalová, 2002), substrate characteristics (Lacoul & Freedman, 2006b;Mikulyuk et al, 2011), water-level fluctuations (Fernández-Aláez et al, 1999Van Geest et al, 2005), land uses in the catchment (Capers et al, 2010;Akasaka et al, 2010) or propagule dispersal (Dahlgren & Ehrlén, 2005). In organisms with high dispersion capacity, local environmental conditions can be expected to explain a large proportion of the assemblage composition (Capers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%